Study on properties and mechanism of organic montmorillonite modified bitumens: View from the selection of organic reagents. (30th August 2019) - Jia, Meng; Zhang, Zengping; Wei, Long; Wu, Xingjiao; Cui, Xin; Zhang, Hongliang; Lv, Wenjiang; Zhang, Qiang
Graphical abstract: Highlights: Organic treatments to MMT usually contribute to better properties of bitumen as compared to untreated MMT. Bitumen molecules have successfully intercalated into galleries of MMT and OMMTs. Increasing molecular chain length of organic reagent is more helpful to the improvement of asphalt properties than introduction of benzyl groups. Abstract: Organic reagents, as modifiers of montmorillonite (MMT), have great effects on bitumen properties. In this respect, octadecyl dimethyl benzyl ammonium chloride (1827), stearyl trimethyl ammonium chloride (1831) and dodecyl trimethyl ammonium chloride (1231) were selected to modify MMT. The MMT and three kinds of organic montmorillonite (OMMT) were then used to modify base bitumen. Structures of MMT and OMMTs were tested by scanning electron microscope (SEM) and X-ray Diffraction (XRD). Results show that organic treatments contribute to the expansion of MMT interlayer space and make lamellar edges of OMMTs more regular without obvious curls. Properties of modifiers and modified bitumens were studied mainly by hydrophilicity test, physical tests, dynamic shear rheometer (DSR) and bending beam rheometer (BBR). It is found that introduction of MMT and OMMTs improves high temperature property but weakens low temperature property of bitumen. 1827-OMMT modified bitumen exhibits the best high temperature property, followed by 1831-OMMT modified bitumen, while there is better low temperature property for 1831-OMMT modified bitumen than 1827-OMMT modified bitumen. Moreover, 1827-OMMT modified bitumen and 1831-OMMT modified bitumen all show excellent storage stability. Modification mechanism and micro-morphologies were tested by XRD, Fourier transform infrared spectroscopy (FTIR) and atomic force microscope (AFM). Results show that bitumen molecules can intercalate into interlayer spaces through reacting with exchangeable cations in interlayers. Only 1831-OMMT and 1827-OMMT modified bitumens form the exfoliated nanostructures.